A Recombinant Viral Hemorrhagic Septicemia Virus Genotype IVb Glycoprotein Produced in Cabbage Looper Larvae Trichoplusia ni Elicits Antibody Response and Protection in Muskellunge. Issue 2 (3rd May 2017) - Standish, Isaac; Faisal, Mohamed
Abstract: The Novirhabdovirus viral hemorrhagic septicemia virus (VHSV) genotype IVb has caused serious fish kills and become endemic throughout the Great Lakes basin of North America. This is troublesome since there are no protective vaccines currently approved against this deadly disease even though recombinant technology has become increasingly common. Herein, we explored the production of a recombinant VHSV‐IVb glycoprotein, believed to be important for virus infectivity, and determined its ability to elicit protection against challenge with the wild virus strain. A recombinant baculovirus containing a 5′ 6x polyhistidine tag embedded in the VHSV‐IVb G gene was used to infect the larvae of the cabbage looper Trichoplusia ni . A sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS‐PAGE) of affinity‐purified protein yielded apparent VHSV‐IVb glycoprotein at the expected molecular weight of 65 kDa. The recombinant protein (rG) was used successfully in coating microtiter plate wells in an indirect enzyme‐linked immunosorbent assay (ELISA), and positive anti‐VHSV‐IVb antibodies in Muskellunge Esox masquinongy were capable of binding to both the rG and purified whole VHSV‐IVb, indicating epitope resemblance. In addition, the rG elicited a protective response in Muskellunge during a VHSV‐IVb immersion challenge, resulting in 80% relative percent survival. Our results demonstrate that cabbage looper larvae can serve as an excellent production system for apparently conformationally correct viral glycoprotein. The incorporation of a polyhistidine tag facilitates obtaining highly purified protein in a relatively high concentration, which has potential in the development of an efficacious subunit vaccine against this deadly virus. Received September 11, 2016; accepted March 10, 2017 Published online May 3, 2017